Recursos personales y resiliencia en adolescentes sin cuidados parentales - Diaz Sono, Valeria (2022)
The general objectives of this study are to describe the experience of adolescents before and during their stay in the Residential Shelter Center [CAR], to identify personal resources, and to analyze the characteristics of the resilience of adolescents without parental care. The type of research is qualitative and the design is phenomenological. In addition, the participants, both men, and women, range between 12 and 17 years old and belong to a CAR in Lima. Likewise, a semi-structured interview consisting of 22 guiding questions and an activity to complete sentences were used as a data collection technique. For the analysis of the information collected, the reduction of all the information, a descriptive analysis, and the interpretation of the information described in the previous points were carried out. Finally, 3 categories were obtained as results: adolescent experience, personal resources and resilience. It is concluded that adolescents have had dysfunctional family experiences in the past; however, they currently have an adaptive environment supported by their siblings and the CAR in which they reside. It was also found that the sample has 5 personal resources (self-knowledge, desire for personal change, emotional intelligence, future time perspective, and sense of humor). Finally, 3 elements of resilience were found: type of problems, environmental influences, and how the adolescent copes with adverse situations.